Energy Taxis Is the Dominant Behavior in Azospirillum brasilense - Alexandre, Gladys (American Society for Microbiology, 2000)
Energy taxis encompasses aerotaxis, phototaxis, redox taxis, taxis to alternative electron acceptors, and chemotaxis to oxidizable substrates. The signal for this type of behavior is originated within the electron transport system. Energy taxis was demonstrated, as a part of an overall behavior, in several microbial species, but it did not appear as the dominant determinant in any of them. In this study, we show that most behavioral responses proceed through this mechanism in the alpha-proteobacterium Azospirillum brasilense. First, chemotaxis to most chemoeffectors typical of the azospirilla habitat was found to be metabolism dependent and required a functional electron transport system. Second, other energy-related responses, such as aerotaxis, redox taxis, and taxis to alternative electron acceptors, were found in A. brasilense. Finally, a mutant lacking a cytochrome c oxidase of the cbb(3) type was affected in chemotaxis, redox taxis, and aerotaxis. Altogether, the results indicate that behavioral responses to most stimuli in A. brasilense are triggered by changes in the electron transport system.